Numerical solution of a problem on bending oscillation of a rod - Bukenov, M.; Ibrayev, A.; Zhussupova, D.; Azimova, D. (Publ.KarSU, 2017)
In article considered the problem of curved rod fluctuation with JungвЂTMs module. Shown the civility of the problem formulation. For solution used integro – interpolation method. Constructed implicit differential scheme, which realized by five – point sweep method. Conducted numerical calculations showed coincidence of theoretical calculation values of solution. Calculations conducted on the system of computer algebra Wolfram Mathematica. Results of calculations are given for two cases of fixing ends of the rod: both ends are fixed and one end is fixed other is free.
Сымның иiлмелi тербелiс есебiнiң сандық шешiмi
Численное решение задачи об изгибном колебании стержня
Keywords: difference scheme; pentadiagonal sweep method; oscillations of a rod; YoungвЂTMs module; integro-interpolation method